The Impact of Entrepreneurship Education on the Construction of Entrepreneurial Self-identity of University Students in Egypt - Hala Wasef Hattab; Omar Abdelsalam Fahmy (International Journal of Business and Social Science Research, 2022)
Due to the rise in the number of entrepreneurship education programs that are believed to have an impact beyond creating entrepreneurial knowledge and the multiple attempts to understand the entrepreneurial identity and how it is constructed, the current research aims at investigating the relationship between entrepreneurship education and entrepreneurial self-identity construction for university level-students, hence utilized two measures, the first one asked students whether they define him or herself in an entrepreneurial role or not (Hoang and Gimeno, 2015) and the second one was concerned about the social identity and measured it using the “Identity-scale” developed by Sieger et al. (2016).A self-administered questionnaire was distributed to a sample of 550 students, whereas 280 received formal entrepreneurship education and 270 did not. Results showed that entrepreneurship education had a direct impact on the construction of entrepreneurial identities of university students. However, the impact was of a very low level not exceeding 3.1%, implying the existence of other non-entrepreneurship education-related factors that might contribute to entrepreneurial identity construction to a higher extent.